Neuroglobin: From structure to function in health and disease. (December 2016) - Ascenzi, Paolo; di Masi, Alessandra; Leboffe, Loris; Fiocchetti, Marco; Nuzzo, Maria Teresa; Brunori, Maurizio; Marino, Maria
Abstract: In 2000, the third member of the globin family was discovered in human and mouse brain and named neuroglobin (Ngb). Ngb is a monomeric 3/3 globin structurally similar to myoglobin and to the α- and β-chains of hemoglobin, however it displays a bis-histidyl six-coordinate heme-Fe atom. Therefore, ligand binding to the Ngb metal center is limited from the dissociation of the distal His(E7)64-Fe bond. From its discovery, more than 500 papers on Ngb structure, expression, reactivity, and localization have been published to highlight its biochemical properties and its role(s) in health and disease. In vivo experiments have shown that increased levels of Ngb significantly protect both heart and brain from hypoxic/ischemic and oxidative stress-related insults, whereas decreased Ngb levels lead to an exacerbation of tissue injuries. Although some contradictory data emerged, human Ngb overexpression has been hypothesized to protect neurons from mitochondrial dysfunctions and neurodegenerative disorders such as Alzheimer's disease, and to play a shielding role in cancer cells. Recently, the recognition of Ngb interactors and inducers enlarges the functions of this stress-inducible globin, opening new therapeutic approaches to prevent neuronal cell death. Here, structural and functional aspects of human Ngb are examined critically to highlight its roles in health and disease.